Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

$$ \mbox{How to show that that}\qquad \sum_{n = 1}^{\infty}\left({1 \over 3n - 1} + {1 \over 3n - 2} - {2 \over 3n}\right) = \ln\left(3\right)\ {\large ?} $$ $$ \mbox{or}\quad 1 + \frac{1}{2} -\frac{2}{3} + \frac{1}{4} + \frac{1}{5} - \frac{2}{6} +\frac{1}{7} + \frac{1}{8} - \frac{2}{9} \cdots = \ln\left(3\right) $$

share|cite|improve this question
up vote 18 down vote accepted

Use the fact that $ \displaystyle \frac{1}{m+1} = \int^1_0 x^m dx$ to get $$ \sum_{n=1}^{\infty} \int^1_0 \left( x^{3n-2} + x^{3n-3} -2 x^{3n-1}\right) dx$$

$$ = \int^1_0 \sum_{n=1}^{\infty} \left( x^{3n-2} + x^{3n-3} -2 x^{3n-1}\right) dx$$

$$= \int^1_0 \frac{ x+1-2x^2}{1-x^3} dx= \int^1_0 \frac{2x+1}{x^2+x+1} dx = \log (x^2+x+1) \biggr|^1_0=\log 3.$$

share|cite|improve this answer
How in the world did you ever think of this. – chharvey Sep 16 '12 at 23:30
@TestSubject528491 It is a trick worth keeping in mind. This problem has many variants (sums of 1/(kn+m) where each sum would diverge individually but the cancel out enough to converge) and this method can be used on them all, which is the main reason I've remembered it, but it is also used to find expressions for generating functions/power series. I can't think of great examples off the top of my head sorry but here's another thread where it comes up. – Ragib Zaman Sep 17 '12 at 0:50
I learned something new today. Thanks, @RagibZaman. – Potato Sep 22 '12 at 17:52

Let $s_N=\sum_{n=1}^N \frac1n$ be the $n$th partial sum of the harmonic series. Then $$\sum_{n=1}^N(\frac1{3n-1}+\frac1{3n-2}-\frac2{3n})=\sum_{n=1}^N(\frac1{3n-1}+\frac1{3n-2}+\frac1{3n})-\sum_{n=1}^N\frac1n=s_{3N}-s_N.$$ It is well-known that $s_N=\ln N +\gamma+O\left(\frac1N\right)$, hence $$\sum_{n=1}^N(\frac1{3n-1}+\frac1{3n-2}-\frac2{3n})=\ln(3N)-\ln N+O\left(\frac1N\right)=\ln3+O\left(\frac1N\right).$$

share|cite|improve this answer

Let's try one line proof using Riemann sums. So, our limit may be written as

$$\lim_{n\to\infty}\sum_{k=1}^{n} \left(\frac1{3k-2}+\frac1{3k-1}+\frac1{3k}-\frac1k\right)=\lim_{n\to\infty}\frac{1}{n}\sum_{k=1}^{2n}\frac1{1+\frac{k}{n}}=\int_0^2\frac{1}{1+x}=\ln3.$$


share|cite|improve this answer

Let $H_n=\sum_{k=1}^n \frac1k$ denote the $n$-th harmonic number.

It is well known that $H_n \sim \ln n + \gamma$, where $\gamma$ is Euler-Mascheroni constant. (To be more precise, $\lim\limits_{n\to\infty} (H_n-\ln n) = \gamma$, which is what we actually need below.)

You are interested in $$\sum_{k=1}^n \left(\frac1{3k-2}+\frac1{3k-1}+\frac1{3k}-\frac3{3k}\right) = H_{3n}-H_n \sim \ln{3n}-\ln n = \ln 3.$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.